SOME NEW RESULTS OF A FRACTIONAL VON BERTALANFFY MODEL - AL-SAFFAR, AVAN (E-Jurnal Matematika; Vol 12 No 3 (2023), 2023)
In this article, we review the deterministic and perturbed Von Bertalanffy model that has been developing to discuss the existence and uniqueness results of the model. The key research issues are highlighted, and the results and interpretations are summarized. We investigate the effects of changing some of the system's control parameters through numerical simulations. We resolve the Von Bertalanffy ordinary differential equation of fractional order. The analytical solution is obtained.